Streamlining Investment Governance in Indonesia’s Capital: The Role of PTSP–OSS in Enhancing Legal Certainty in DKI Jakarta - Leonard Luther Wong; Triandharma Ponto; Salsa Augesca Onasis; Russell Liang (Syntax Corporation, 2026)
This research analyzes the effectiveness of the investment and business licensing regulatory framework in DKI Jakarta through the integration of the One-Stop Integrated Service (PTSP) with the Online Single Submission Risk-Based Approach (OSS-RBA) in ensuring legal certainty for investors. As Indonesia's primary economic center, DKI Jakarta requires regulatory efficiency and legal certainty to support its investment climate. This research adopted a normative juridical method by examining key regional regulations governing investment and licensing in Jakarta, including Governor Regulation No. 7 of 2025 on the Implementation of Investment and One-Stop Integrated Services, Governor Regulation No. 32 of 2018 on Investment Information, Promotion, and Cooperation, Governor Regulation No. 92 of 2020 on Regional Investment Management, Governor Regulation No. 147 of 2018 on Building and Infrastructure Licensing, and Regional Regulation No. 13 of 2024 concerning Regional Capital Participation. These regulations collectively form an institutional framework designed to simplify licensing procedures, centralize administrative services, and enhance investor confidence. The study also considers the distribution of investment across key regions in Jakarta, particularly logistics and port-related activities in North Jakarta, property and commercial developments in West Jakarta, and office as well as mixed-use developments in South Jakarta. The findings indicate that the integration of PTSP with the OSS-RBA system has contributed to reducing administrative complexity and increasing transparency, although challenges related to inter-agency coordination remain. Overall, Jakarta’s regulatory framework plays a positive role in creating an investor-friendly environment and supporting sustainable regional economic development.